Urban Sprawl Policies - محمد نافع السيد , منى; عبد المجيد السلام, أ.م.د. نادية (Journal of Planner and Development, 2016)
The majority of countries in the world suffer from rapid urbanization, which is associated with many problems as a result of the absence of integrated regional policies of development. One of the most important solutions is urban sprawl, a decentralization way to overcome the effects and problems of rapid urbanization. Hence the research problem in the lack of clarity of urban sprawl policies to solve the problem of overcrowding and overpopulation. The objective of the research is to determine the urban sprawl policies to solve the problem of overcrowding and overpopulation, the research hypothesis is that urban sprawl policies actively contribute to solving congestion and overpopulation problems. The research has come to define these policies and analyze an experience for each of them extracting the elements of success or the reasons for its failure to come up with the useful results in the success of those policies in solving the problem of overcrowding and overpopulation.